PENGARUH PEMUPUKAN FOSFOR DAN KALSIUM TERHADAP SERAPAN HARA DAN PRODUKTIVITAS DUA GENOTIPE KEDELAI PADA BUDIDAYA KERING - Toyip H (Agropet, 2012)
The objectives of this research were to study the effect rates of P and Ca fertilizers on productivity and nutrient uptake of two soybean genotypes in dry culture. The experimental design was split split plot with three factors i.e. phosphorus, calcium and genotype planted in dry culture. Dry culture with phosphorus fertilizer application (72 kg P¬2O5/ha) increases the number of filled pods and grain weight per plot. Number of pods of Tanggamus variety was greater than Anjasmoro variety. Liming had no effect on productivity. Path analysis showed that largest direct effect to grain weight were plant height and leaf weight. Increased rate of P and Ca fertilizer increased the uptake of P and Ca, but variety Tanggamus is more responsive than variety Anjasmoro. Interaction of phosphorus fertilizer 72 kg P¬2O5/ha with lime 1 ton/ha increased grain weight per plot. Largest direct effect on increasing grain weight is plant height and the number of branches. Phosphorus application (72 kg P¬2O5/ha) and liming (1 ton/ha) also give highest uptake of P and Ca